A Natural Gas Severance Tax—An Economic Analysis. Issue 12 (11th September 2014) - Kinnaman, Thomas C.; Veser, Götz
Abstract This study estimates the economic effects of a severance tax on the market for natural gas produced from shale sources using non‐conventional extraction methods, such as horizontal drilling and fracking. Results suggest that a severance tax of 5 % would increase the price of natural gas by as much as 3.82 % and decrease gas extraction by an estimated 1.16 % to a value of 9.52 %. If applied to the Commonwealth of Pennsylvania in the United States, a 5 % severance tax is estimated to raise between US 443 and 486 million per year in public revenue. The marginal deadweight loss associated with a 5 % severance tax is estimated between 1.27 % and 12.85 % of the last dollar earned. The burden of this tax falls on both producers and consumers and depends upon the underlying assumptions made regarding the price responsiveness of consumers and producers. Under plausible assumptions, a family consuming 1000 MMcfs (≈2.8×104 m3) per year of natural gas is estimated to pay an additional 100 per year after the implementation of a 5 % severance tax.